Volumetric Symmetry after Unilateral Autologous Breast Reconstruction: A Reasonable Goal - Glener, Adam D. (Plast Reconstr Surg Glob Open, 2019)
With growing concerns about the overuse of contralateral prophylactic mastectomy, optimizing unilateral mastectomy reconstruction outcomes becomes a priority. However, there remains a paucity of objective data that describe volumetric symmetry between a natural and autologous-reconstructed breast. METHODS: We evaluated patients who underwent unilateral mastectomy reconstruction with free-flap abdominal tissue transfer from 04/2006 to 01/2015, and had at least 2 postoperative magnetic resonance images (MRIs; n = 28). Using these MRI data, volumetric measurements of the reconstructed and natural breast were performed at the first postoperative MRI (after all revisions were complete) and the most recent MRI. Relationships were analyzed using Spearman correlation coefficients. A symmetry score (SS) was calculated such that values closer to 1.0 reflected volumetric symmetry. RESULTS: The mean age (years) and BMI of the patients was 44.8 and 26.8, respectively. The mean interval time between the MRIs was 3.03 years (range 0.43–6.6). After surgical revisions were complete, volumetric symmetry between reconstructed and nonreconstructed breasts was typically achieved (mean SS 0.92). This symmetry was also retained at the end of follow-up (mean SS 0.96), despite a mean change in BMI of 3.9% (range 1.1–7.7). Additionally, the mean number of flap revisions was 0.75 (range 0–2), and 39% of patients had a procedure performed on the natural breast. CONCLUSION: In patients undergoing unilateral abdominal-based breast reconstruction, volumetric symmetry is attainable; however, it can require flap revisions and procedures to natural breast. Interestingly, this study does show that initial symmetry is retained postoperatively, regardless of changes in BMI.